Comparative study on conventional and improved integrated farming systems for sustainable production, income generation and employment opportunity among the tribal farmers in hilly Regions of Manipur - ANSARI, M A; PRAKASH, N; BAISHYA, L K; PUNITHA, P; YADAV, J S; SHARMA, P K; SAILO, BLESSA; ANSARI, M H (The Indian Journal of Agricultural Sciences, 2026)
Farming system integrates livestock farming and agriculture. It has revolutionized conventional farming of livestock, the practice of cultivating the land and raising stock and the aquaculture, horticulture, agro-industry and allied production activities. It is playing a pivotal role in maintaining the sustainability and increases the productivity as well as provides employment for better livelihood. The present survey was carried out in Chandel, Churachandpur and Ukhrul hill districts of Manipur during 2012-13. A total of 70 farmers/district, with a cluster of thirty five farmers for improved integrated farming systems (IIFS) and thirty five for conventional farming system (CFS) were surveyed for this study. The average holding of each farmer was 0.64 ha in Chandel, 0.65 ha in Churachandpur and 0.87 ha in Ukhrul. Seven components, i epaddy, vegetables, fruits, piggery, backyard poultry, fishery and water management were studied. Among hill districts, Ukhrul had higher production of all enterprises. The results revealed that the performance of all components is better in IIFS than CFS. The average productivity of different enterprises was significantly higher in IIFS as compared to the CFS. The IIFS also gave higher net returns and benefit cost ratio to the farmers as compared to traditional farming. In farming system most of the activities were done by women, therefore they were employed more than men. The overall result revealed that the improved practice with different crop and animal components is an excellent approach for sustainable production, income generation and employment opportunity of the small and marginal rural households of Manipur.